The Effect of Dividends, Firm Size, Funding Decisions and Return on Equity on Firm Value With Liquidity as Moderating Variables in Manufacturing Companies on The Indonesia Stock Exchange for The Period of 2018-2020 - Annisa Nauli Sinaga; Efendy Lim; Katherine Andresen; Trisna Ceria Waruwu (Kusuma Negara Business School, 2022)
This study aims to examine and analyze the effect of Dividend Policy, Firm Size, Funding Decisions and Return on Equity have an influence on firm value with liquidity as a moderating variable in manufacturing companies on the Indonesia Stock Exchange for the 2018-2020 period. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is all manufacturing sector companies listed on the Indonesia Stock Exchange totaling 207 companies. The sample of this research is 37 companies with purposive sampling technique. The data analysis method used is multiple linear regression. The results of the f test where F arithmetic > F table (3.509 > 2.46), then H1 is accepted, meaning that because F arithmetic is greater than F table and Significant does not exceed 0.05, it can be concluded that there is a significant simultaneous positive effect between Dividend Policy, Firm Size, Funding Decision, Return on Equity, Interaction of Dividend*Liquidity Policy, Interaction of Dividend*Liquidity Policy, Interaction of Company Size*Liquidity, Interaction of Funding*Liquidity, and Interaction of Return on Equity*Liquidity to Firm Value in Manufacturing Sector Companies on the Stock Exchange Indonesian Securities for the period 2018-2020. The results of the t test show that only return on equity has an effect on firm value, the rest has no effect and is significant on firm value. obtained the Adjusted R Square value of 0.170 or equal to 17%, it can be said that the variable ability of Dividend Policy, Company Size, Funding Decision, Return on Equity, Interaction of Dividend*Liquidity Policy, Interaction of Dividend*Liquidity Policy, Interaction of Firm Size*Liquidity, Interaction Funding Decision*Liquidity, and Interaction of Return on Equity*Liquidity in explaining Firm Value is 17% while the remaining 83% (100% - 17%) is explained by other variables outside of the variables studied.